Mehmed Uzun as a Representative of Modern Kurdish Narrative - Abdulkarim, Chiad A.; Saeed, Ismael (Humanities Journal of University of Zakho, 2019)
This article is dedicated to the analysis of Mehmed Uzun’s initial Two novels, Tu (1985) and Mirina Kalekî Rind (1987). It focuses on Mehmed Uzun as a representative of modern Kurdish narrative. When it comes to the concepts of identity distortion in characters and their complicated state of mind, his novels can be a relevant subject matter for interpretation. In light of Mikhail Bakhtin’s theory of polyphony and the scholars who worked in his circle, this article explores the polyphonic aspects of Mehmed Uzun’s two initial novels. Through novelistic discourse analysis, it becomes apparent that the characters suffer from the dormant identity, which is locally given to them in Uzun’s diasporic fiction. Next, the discussion gives further details regarding polyphony and how problematic polyphony can be found in the novels mentioned above. Finally, this article sheds light on the notion of identity formation in the fictional novel and its relationship with the real world during the time the novels were written. It concludes that the entire representation of characters and settings in his novels leads to the production of a realistic novel with the consistent discourse that can be considered an objective view of a specific time in history which is undermined.